2020
DOI: 10.1186/s43141-020-00095-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking and simulation investigation: effect of beta-sesquiphellandrene with ionic integration on SARS-CoV2 and SFTS viruses

Abstract: Background At present, viral diseases become major concern for the world. SARS-CoV2 and SFTS viruses are deadly in nature, and there is a need for developing best treatments for them. Modern in silico approaches were found to be very handy in determining putative drug molecules. In this study, we analyze interaction of beta-sesquiphellandrene (compound belongs to ginger) with spike protein (Sp) and membrane glycoprotein polyprotein (MPp). Results Our molecular docking and simulation study reveals the perfect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Recent developments in immunoinformatics show novel ways to predict epitope-based vaccine candidates and therapeutics against many harmful pathogens like Candida auris [ 35 ] and human cytomegalovirus [ 38 ]. Similarly, drug repurposing was made easy against harmful pathogens by deploying bioinformatic approaches [ 39 ]. Similarly, for animal models, viral pathogenic proteomes were screened for vaccine designing by deploying immunoinformatics [ 33 , 36 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in immunoinformatics show novel ways to predict epitope-based vaccine candidates and therapeutics against many harmful pathogens like Candida auris [ 35 ] and human cytomegalovirus [ 38 ]. Similarly, drug repurposing was made easy against harmful pathogens by deploying bioinformatic approaches [ 39 ]. Similarly, for animal models, viral pathogenic proteomes were screened for vaccine designing by deploying immunoinformatics [ 33 , 36 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“… 44 The results from a computational analysis indicate that a ginger-derived terpene namely sesquiphellandrene binds to S protein and thus interferes with the S protein-ACE2 interaction. 45 It is obvious that these docking computational studies must be supported by in vitro and in vivo observations.…”
Section: Evidence Of Ginger's Potentials Against Covid-19mentioning
confidence: 99%
“…CADD (Computer-aided-drug-designing) approaches in therapeutic predictions revealed seq1(RHDEEEEKAKV),seq3(KSNSTVEISQNVQSVDSSKM),seq4(KQVAEMNKPAVGSKTSDANHDLKS),seq5(KTKSAGNDSIQSTKPVPSALTVDKA),seq6(RELEDSNIHHVAASVVLESKSSRT), and seq8(LYSKVELHPFGLHNLGNSCYANAVFSV), shows interaction with chitin, a major constituent of fungal cell wall.A CADD study was also found successful in many recent studies, where plant constituents were found to be effective against Sars-Cov2 (Joshi et al 2020 ). P. cineraria was recently found to have one important chemical constituent vitexin that plays major role in inducing apoptosis of leukemia cells (Sarkar et al 2021 ).…”
Section: Discussionmentioning
confidence: 95%